The Turk in America : creation of an enduring prejudice - McCarthy, Justin (Utah series in Turkish and Islamic studies, 2010)
"In The Turk in America, historian Justin McCarthy seeks to explain the historical basis for American prejudice towards Turks in the nineteenth and early twentieth centuries. The volume focuses on fraudulent characterizations of Turks, mostly stemming from an antipathy in Europe and America toward non-Christians, and especially Muslims. Spanning one hundred and fifty years, this history explores the misinformation largely responsible for the negative stereotypes of Turks during this period"--Publisher description.
Keywords: Armenian massacres, 1915-1923 : Foreign public opinion, American; Missionaries : Turkey : History; Missions to Muslims : Turkey : History; Prejudices : United States; Public opinion : United States; Stereotypes (Social psychology) : United States; Turks : Public opinion; armenialaiset; etniset puhdistukset; turkkilaiset; Turkey : Foreign public opinion, American; Turkey : Relations : United States; United States : Relations : Turkey; Turkki; Yhdysvallat